Nitrogen utilization in heterotrophic Chlamydomonas reinhardtii - Sweeley, Justin Brye, author; Reardon, Kenneth F., advisor; Peebles, Christie, committee member; Snow, Christopher, committee member; Peers, Graham, committee member (Colorado State University. Libraries, 2017)
The aim of this dissertation research is to bring better understanding to the process of nitrogen adaptation in heterotrophic Chlamydomonas reinhardtii. Microalgae are a diverse group of aquatic photosynthetic organisms that account for almost 50% of the photosynthetic productivity on Earth. There is immense interest in using the unique ability of microalgae to convert sunlight to triacylglycerides (TAGs) for industrial purposes. However, to date there has been little success in implementing these systems at scale and price parity with non-biological methods. Microalgae can modify their metabolism to adapt to the surrounding environment. Under certain circumstances, including nutrient stress, microalgae divert carbon flow away from biomass production and into TAG accumulation. The most common nutrient stress used to trigger TAG accumulation is nitrogen stress, most often induced by transferring a cell from a nitrogen replete medium to a deficient one. The goals of this research were to understand this process, develop methods to manipulate the stress response, and ultimately, to find a way to decouple lipid production from nutrient depletion entirely. Chapter 1 introduces the concepts and research referenced throughout the dissertation including: a background of the C. reinhardtii species, the cultivation techniques that have been applied to cultivation, the physiology behind nitrogen stress, the mechanism that algae use to incorporate nitrogen into the cell, and finally an introduction to the global nitrogen regulator, PII. Chapters 2 through 4 present research into the nitrogen stress pathway and its modification. Chapter 2 discusses a simple method of cultivation used to bring about new insights into the nitrogen stress response, as well as a proposed technique for increasing cellular lipid production. Through differential nitrogen feeding, significantly different effects on cell growth were observed, demonstrating that the response to nitrogen availability is a continuous effect as opposed to an all or nothing "stress response". Chapter 3 describes experiments in which C. reinhardtii was genetically modified to increase understanding of the nitrogen stress response. A nitrogen regulatory protein, PII, was downregulated via amiRNA. Cultures of a mutant strain with lower levels of PII exhibited slow adaptation to fresh nutrient-replete medium but achieved a higher final cell number, final mass concentration, and total neutral lipid content. Similar results were obtained in cultures shifted to nitrogen-free medium. Chapter 4 employs proteomics to identify differences in the specific protein expression pattern between a functional PII strain and a knock-down mutant. Chapter 5 demonstrates a unique approach to producing an engineered nutrient-limited environment in a continuous stirred tank bioreactor. Chapters 7 and 8 summarize the research findings and offer possible direction for future research. Through this research work, new information was obtained on the effects of PII on the cellular response to nitrogen limitation. By increasing our understanding of this basic mechanism, we have proposed several processing conditions that may be implemented to increase microalgal productivity. Furthermore, the homology between microalgae and terrestrial plants suggests the possibility that the results discussed within could give genetic engineers new targets for creating crops with decreased nitrogen demands and increased nitrogen-stress tolerance traits.
Keywords: chlamydomonas; nitrogen starvation; proteomics; nitrogen; algae; PII